Priorização de investimentos em sistemas de distribuição de energia elétrica de baixa tensão - Almeida Filho, Aurino (2003)
A modern methodology applied with evolving computing techniques has been developed, through genetic algorithm, as well as branch and bound, to prioritize the works for the improvement of low voltage circuits, so that customers service can be adequate aiming at optimizing the resources available in order to be in accordance with law demands, and to maximize the investment s results. Many times, the resources available are not sufficient to perform the improvements needed all at once, or even the concessionaire does not have physical capacity to accomplish them, so it becomes necessary to prioritize them. The methodology developed embodies the load flow analysis of secondary network circuits, and the demands and penalties imposed by the regulator department. Besides, it also embodies a probabilistic approach that has been included considering several customers typical load curves (residential,commercial, industrial, and public lighting). The optimization is performed through of the software developed - Apriori, through the analysis of all existing improvements, prioritizing the ones that provide better investment results, as well as that are in accordance with voltage levels criteria, and can be continuously working according to the law, and to the budget imposed by the concessionaire. Generally, the amount of improvements represents a global cost that exceeds such availability. Therefore, not all of them are set out for the works performance. The simulations are basically performed in two stages: the first is responsible for secondary network circuits, using power flow, aiming at identifying the improvements needed, and using the planning criteria in order to accomplish the needs of the concessionaire and its customers and in the second stage, the prioritization of several improvements is accomplished itself, considering law demands, fines for not following them, availability of the concessionaire s resources, and all costs of the enterprise, both the ones that are under the responsibility of the concessionaire, and the ones imposed to the customers due to low quality services.